(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article deals with the issues of effective leadership in different organizations. The authors describe and analyze the elements of situational leadership and consider the relationship between personal characteristics of a person and his leadership abilities. Illustrative examples of leadership qualities in different historical persons are given